A randomised crossover trial of closed loop automated oxygen control in preterm, ventilated infants. (6th October 2020) - Sturrock, Sarah; Ambulkar, Hemant; Williams, Emma E.; Sweeney, Samantha; Bednarczuk, Nadja F.; Dassios, Theodore; Greenough, Anne
Abstract: Aim: To determine whether closed loop automated oxygen control resulted in a reduction in the duration and severity of desaturation episodes and the number of blood gases and chest radiographs in preterm, ventilated infants. Methods: Infants were studied on two consecutive days for 12 hours on each day. They were randomised to receive standard care (standard period) or standard care with a closed loop automated oxygen control system (automated oxygen control period) first. Results: Twenty‐four infants with a median gestational age of 25.7 (range 23.1‐32.6) weeks were studied at a median postconceptional age of 27.4 (range 24.3‐34.9) weeks. During the automated oxygen control period, there were fewer desaturations that lasted >30 seconds ( P  = .032) or >60 seconds ( P  = .002), infants spent a higher proportion of the time within their target SpO2 range during the automated oxygen control period ( P  < .001), and fewer manual adjustments were made to the inspired oxygen concentration (mean 0.58 vs mean 11.29) ( P  < .001). There were no significant differences in the number of blood gases ( P  = .872) or chest radiographs ( P  = .366) between the two periods. Conclusion: Closed loop automated oxygen delivery resulted in fewer prolonged desaturations with more time spent in the targeted oxygen range.